Incidence, predictors, and clinical outcomes of early stent thrombosis in acute myocardial infarction patients treated with primary percutaneous coronary angioplasty (insights from the University of Ottawa Heart Institute STEMI registry). Issue 5 (22nd July 2017) - Singh, Kuljit; Rashid, Mohammed; So, Derek Y.; Glover, Christopher A.; Froeschl, Michael; Hibbert, Benjamin; Chong, Aun‐Yeong; Dick, Alexander; Labinaz, Marino; Le May, Michel
Abstract: Background: Early stent thrombosis (ST) remains an important complication of primary percutaneous intervention (PCI). To date, our information on angiographic and clinical predictors of early ST in ST‐segment elevation myocardial infarction (STEMI) patients treated with primary PCI is limited. Methods: We tried to evaluate the incidence, predictors, and outcomes of early ST in real‐world patients treated with primary PCI. We identified all the patients presenting with STEMI between June 2004 and January 2011 who underwent primary PCI as the primary mode of revascularization. Diagnosis of ST was made as per the standard definition proposed by the Academic Research Consortium. Results: The incidence of early ST was 1% among 2, 303 patients treated with primary PCI. Definite and probable early ST occurred in 22 and 2 patients, respectively. Patients with early ST had higher in‐hospital ( P  = 0.03) and 30‐day mortality ( P  = 0.048). The rate of cardiogenic shock ( P  = 0.0006) and cerebrovascular accident ( P  = 0.0004) was also greater in the early ST group. Smaller stent diameter and lower use of intracoronary glycoprotein IIb/IIIa inhibitor were associated with higher rate of early ST. There was a trend of higher bivalirudin use in ST group, which did not reach significance ( P  = 0.07) On IVUS imaging, stent malapposition and uncovered plaque area were noted in 6 out of 11 cases. Conclusion: The incidence of early ST in primary PCI cohort is low. However, it is still associated with higher mortality and morbidity. Small stent diameter and disuse of intracoronary glycoprotein IIb/IIIa inhibitor may be associated with early ST.